Pedagogical design for knowledge creating inquiry in customer projects - Hanni Muukkonen; Kari Kosonen; Pentti Marttiin; Petri Vesikivi; Jyrki Kaistinen; Göte Nyman (Knowledge Management & E-Learning: An International Journal, 2013)
Two higher education courses involving students, teachers, and customers in multifaceted experiences of knowledge creation are described. The Trialogical Learning Approach (TLA) provides a theoretical framework to address learning and teaching organized around authentic problems and the development of shared knowledge objects, such as reports, products, and new practices. The approach directs attention to those aspects of social interaction and artifact-mediated activities, which focus on the development of shared objects and the pursuit of novel knowledge and understanding. The roles of technology-mediation, customer involvement, and guidance in developing effective pedagogical practices for knowledge creation were addressed. It appears necessary to design sufficient open-endedness and complexity for students’ teamwork to generate unpredictable, practical, and epistemologically challenging situations. Pedagogical design for such a process has different foci in the four central phases: planning, project initiation, project execution, and presentation and evaluation. Planning and initiation are central to establishing relevance and project awareness for the collaboration of student teams with a customer. Guidance and expert modeling during project initiation and execution is needed to overcome feelings of uncertainty during a challenging and complex assignment. Mediation provided by collaboration tools facilitates reflection on collective practices, iterative development of knowledge objects, and documentation of the learning outcomes of customer projects.